The Implementation of â€œProsa ABGeâ€ Teaching Model to Improve Speaking Ability - Jwalita, Nitya (ELLITE, 2017)
The result of speaking assessment of adjective clause of Sastra Inggris subjectin semester 1 of 2015/2016 academic year showed that 8 out of 36 studentsof XI MIPA 4 did not pass the minimum criteria. This condition encouragedthe researcher to hold a class room action research. This research combinedProject Based Learning teaching model with Scientific Approach, completedwith gadget to support the teaching learning process. The goals of the researchare to describe how Prosa ABGe teaching model improved the speaking abilityof the students; and to describe how Prosa ABGe teaching model improved thesocial attitude of the students. Both data of speaking ability and social attitudewere taken through observation which was held based on rubrics.